Experimental investigation of adsorption isotherms : a fundamental study - Loo, Mathieu Monford Nian Shan (2014)
In an era of heightened environmental and energy concerns, the ability of traditional cooling technology is limited. However, the application of adsorption cooling technology has the potential to address this gap. The objective of this project is to prove the validity of the Constant Volume Variable Pressure CVVP setup by plotting the uptake versus pressure (isotherm) of RD 2060 silica gel and water. The results obtained are compared with those in existing literature. In this experiment, the pressure within the adsorption chamber is varied by changing the mass of the silica gel. The isotherms are investigated experimentally at temperature ranges in increments of 10 degrees Celsius between 35 to 65 ̊C. Furthermore, the existing CVVP setup was modified to improve the uptake performance. The results were correlated using the Langmuir and Tóth isotherm models. In this experiment, after the existing set up was modified, the maximum experimental uptake as increased to a maximum level of 0.24 grams of water vapour per gram of silica gel. This value was attained at 35 degrees Celsius with 0.337 grams of type RD2060 silica gel. The results obtained were considerably different from those found in existing literature. The probable cause is due to the inability of the heater to maintain a constant temperature.